Communicative functionality in individuals with schizophrenia (Research, Society and Development, 2021)
It is extremely important to discuss mental health, exploring more information and thus raising awareness about the different forms of treatment that these people can acquire. Thus, this article addresses a discussion about mental health, precisely about Schizophrenia and its communicative functionality in patients diagnosed with the disease. The main objective of this research was to investigate the difficulties in communication and language skills, which can affect the interpersonal relationships of individuals diagnosed with schizophrenia. The methodology used for better data investigations for this work was an integrative bibliographic research that allows a better theoretical foundation and a survey of true and critical data. It was found in the performance of tasks by people with schizophrenia, all of them present alterations, with the aspects most affected by issues related to discourse and pragmatics, which should not only be related to linguistic aspects, but also to the characteristics of altered thinking and cognition, affective blunting and social issues related to this disorder.